ANALISIS PRINSIP 5 C’S TERHADAP PEMBERIAN KREDIT PADA PT BANK RAKYAT INDONESIA TBK, CABANG TIMIKA (STUDI KASUS PADA UNIT SIMPANG LIMA SP 2) - Ludia Panggalo (JURNAL ULET (Utility, Earning and Tax), 2018)
The aim of this research are: 1) To know the feasibility of debtor character at PT Bank Rakyat Indonesia, Unit Simpang Lima SP 2; 2) To know the feasibility of debtor capacities; 3) To know the feasibility of capital of the debtor; 4) To know the feasibility collateral (guarantee/collateral) of the debtors; 5) To know the feasibility condition of economy (economic conditions) of the debtor. The researcher used to take two samples being processed filing debtor credit. Data analysis techniques used are as follows: 1) To know the feasibility of the debtor character used table to analyze the character of the debtor; 2) To know the feasibility of capacity (ability) of the debtor used the formula RPC (repayment capacity), namely: RPC = (total revenue minus cost and expenses) x 75%; 3) To know the feasibility of capital of the debtor are used Total Asset to debt ratio; 4) To know the eligibility of collateral (guarantee) of the debtor used the calculation by estimating the sales price guarantee using market value and liquidation value; 5) To know the feasibility condition of economy (economic conditions)of the debtor used the scoring table. The results of research showed that: 1) the feasibility of characters (character/characters) debtor rated by 3 mutation analysis tools that account, BI Checking and checking community. Based on analysis of the character of debtor A and debtor B deserves credit facility. 2) In terms of the capacity of debtor A and B deserves credit for its RPC Rp 3.802.500and Rp1.762.500; 3) The leverage ratio for debtor A and debtor B each 0:04 and 0.0084, financing itself by debtor A and debtor B each 0 and 0; 4) A debtor's total collateral coverage of debtor A and B each 140% and 102,4%; 5) Based on the scoring table, debtor A and debtor B deserves credit. A score value for the debtor A and B each 2, 6 and 4.